RELATIONSHIP OF ZOOM LEARNING METHODS WITH THE STRESS LEVEL OF THE TEACHER IN THE PERIOD COVID-19 PANDEMIC AT SMP NEGERI 6 MEDAN IN 2022 - Vina Yolanda Sari Sigalingging; Rotua Elvina Pakpahan; Wira Agustina Simamora (Jurnal Scientia, 2023)
The COVID-19 pandemic has caused changes to the learning methods used, which previously has to be done face-to-face, now have to be done online. Indirect online learning systems can be taken for granted by teachers, where each teacher must make new habits in its implementation, causing a psychological impact called stress. This study aims to identify the relationship between zoom learning and teacher stress levels during the COVID-19 pandemic at SMP Negeri 6 Medan in 2022. The research method uses a correlation design with a cross sectional design. The study population are 41 people with a total sample of 41 people. The sampling technique used total sampling. Data collection, collected directly by using a questionnaire. The results show that the zoom learning method was in the medium category (44.4%) and the teacher's stress level was in the medium category (48.9%). The results of the Fisher Exact Test found p-value = 0.003 (>0.005), meaning that there is a relationship between the zoom learning method and the stress level of teachers during the COVID-19 pandemic at SMP Negeri 6 Medan in 2022, it is expected that respondents can practice using the Zoom meeting application, so that can increase knowledge in the zoom learning method and can manage stress